Liga Kobiet – organizacja „reprezentująca” interesy kobiet w Polsce Ludowej. Zarys działania - Lubik-Reczek, Natasza; Reczek, Rafał (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
The end of WWII did not bring the freedom Poles had desired so much. The activities of the Communist authorities right after the war resulted from their weakness. Their operations were initially possible thanks to the Red Army, and later on due to the extensive repression system of a Communist state. Under such political circumstances, only political parties and other entities that submitted to the Communist authorities and did not attempt to set new directions or political and social trends were allowed to operate. Operating in the reality of a Communist state, they complied with the vision propagated or recommended as appropriate by the Communist authorities. This was the case of the Women’s League. Established in August 1945, the League was among the first organizations formally registered after the war. It is difficult to evaluate the activities of the Women’s League in the period discussed. The organization operated under the peculiar conditions of a Communist state; what is more, its emergence was even initiated by the structures of this state, aimed at winning over women’s circles in order to legitimize the authorities on the one hand, and to eliminate other women’s organizations, thus giving the League the exclusive right to represent women, as approved by the authorities and in line with their policy. Bearing in mind all the negative aspects of the activities of theWomen’s League, which stemmed from the complex political situation in Poland, the organization made a considerable effort to improve the situation of women.